Taxonomic richness and host range of tropical Asian mussel‐associated mite assemblages (Acari: Unionicolidae) with a description of a new subgenus and species of parasitic mite from freshwater pearl mussels (Unionida: Margaritiferidae). (23rd January 2021) - Chapurina, Yulia E.; Bolotov, Ivan N.; Vidrine, Malcolm F.; Vikhrev, Ilya V.; Lunn, Zau; Chan, Nyein; Win, Than; Bespalaya, Yulia V.; Aksenova, Olga V.; Gofarov, Mikhail Y.; Kondakov, Alexander V.; Konopleva, Ekaterina S.
Abstract: Freshwater pearl mussels (Bivalvia: Margaritiferidae) are among the most imperiled groups of animals globally. While the parasites and symbionts of the Margaritiferidae are rather poorly known, these mussels were thought to be free of parasitic mites (Acari: Unionicolidae: Unionicola ). Here, we report on the discovery of a mite species being associated with the endangered freshwater pearl mussel Gibbosula laosensis (Lea, 1863) from Myanmar. This species, Unionicola ( Gibbosulicola ) sella subgen. & sp. nov., morphologically resembles mites belonging to the subgenera Coelaturicola and Fulleratax (African and Southeast Asian groups, respectively). Our novel discovery expands the host range of Unionicola mites and reveals that all freshwater mussel families of the order Unionida host these aquatic mites. Our phylogenetic research and available published data reveal that the mussel‐associated mite assemblage in Southeast and South Asia contains not less than 17 species and 8 subgenera. Currently, the regional taxonomic richness of this group seems to be largely underestimated. We found that mussel mites from Southeast Asia are narrow host specialists, which are known to occur in a single or a few closely related species belonging to one or two sister genera of freshwater mussels. Finally, our results indicate that mussel mites share generally restricted ranges and that their distribution patterns in Southeast Asia are largely congruent with the boundaries of biogeographic subregions delineated on the basis of phylogenetic studies of freshwater mussels. Abstract : A new mite, Unionicola ( Gibbosulicola ) sella subgen. & sp. nov. (Acari: Unionicolidae), associated with the endangered freshwater pearl mussel Gibbosula laosensis (Lea, 1863) (Unionida: Margaritiferidae), is discovered from Myanmar. The mussel‐associated mite assemblage in Southeast and South Asia contains not less than 17 species and 8 subgenera that are narrow host specialists. The distribution of mussel‐associated mites in tropical Asia is largely congruent with the boundaries of biogeographic subregions delineated on the basis of phylogenetic studies of host freshwater mussels.